2018
DOI: 10.1021/acs.est.7b06692
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Polycyclic Aromatic Hydrocarbons (PAHs) by the Marine Clam, Mactra veneriformis, Chronically Exposed to Oil-Suspended Particulate Matter Aggregates

Abstract: Dispersion and biodegradation of petroleum hydrocarbons are significantly enhanced by formation of oil-suspended particulate matter aggregates (OSAs), but little is known about their adverse effects on benthic invertebrates or microbes. In this study, we investigated: (1) bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) by the marine bivalve, Mactra veneriformis and (2) changes in composition and relative abundances of microbes, during 50-d of an OSAs feeding experiment. Total concentrations of PAHs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…Regardless, consistent with results from this experiment, a number of mussel studies have reported that it would take longer than 25 days for most PACs to reach steady state (Baussant et al, 2001;Enwere et al, 2009;Hwang et al, 2008;Noh et al, 2018;Richardson et al, 2005;Thorsen et al, 2004;H. Wang et al, 2017;Yakan et al, 2011).…”
Section: Pac Toxicokineticssupporting
confidence: 90%
See 1 more Smart Citation
“…Regardless, consistent with results from this experiment, a number of mussel studies have reported that it would take longer than 25 days for most PACs to reach steady state (Baussant et al, 2001;Enwere et al, 2009;Hwang et al, 2008;Noh et al, 2018;Richardson et al, 2005;Thorsen et al, 2004;H. Wang et al, 2017;Yakan et al, 2011).…”
Section: Pac Toxicokineticssupporting
confidence: 90%
“…Some of the PACs increased rapidly during the first few time points of the uptake phase and then slowed down as their concentrations approached steady state while most PACs increased in mussel tissue steadily through time, never approaching steady state. This makes sense as several bivalve exposure studies have reported that it takes longer than 25 days for most PACs to reach steady state (Baussant et al, 2001;Enwere et al, 2009;Hwang et al, 2008;Noh et al, 2018;Richardson et al, 2005;Thorsen et al, 2004;H. Wang et al, 2017;Yakan et al, 2011).…”
Section: Pac Bioaccumulation In Giant Floater Mussels (Pyganodon Gran...mentioning
confidence: 99%
“…are not known hydrocarbon degraders. However, recently, A. sediminis was found to significantly increase in relative abundance when PAHs bioaccumulated in bivalves [112]. Superdispersant 25 resulted in a significant increase in the relative abundance of ASV21 from the genus Neptuniibacter (97.34% 16S rRNA sequence identity to N. marinus strain CECT 8938; Figure 3) after 3 days.…”
Section: Do Dispersants or Biosurfactants Select For Specific Bacterial Genera?mentioning
confidence: 93%
“…Gastropods and bivalves are two different classes of mollusks commonly used as bioindicators (O'Connor, 2002;Rittschof and McClellan-Green, 2005;Noh et al, 2018;Pham et al, 2020). Of these two, bivalves are potentially better suited for biomonitoring due to their sedentary lifestyle and filter-feeding.…”
Section: Introductionmentioning
confidence: 99%